(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This study tries to afford answers to a number of questions that arose concerning the causes and the consequences of the war. What is conspiracy theory? Is there a conspiracy on Syria? Where were the origins of conspiracy theory laid? What was the role that conspiracy played in the war on Syria? Could the war on Syria really be just a result of the conspiracy or were there additional eternal causes? The study concludes that:1. War on Syria was an inevitability that most, if not all, societies will arrive to.2. Creating “ Conspiracy theory” in Syria, is a Conspiracy itself. 3. Believing in Conspiracy is a significant goal of conspiracy itself. 4. Supporting a Conspiracy theory in Syria serves the great powers that invented the theory. 5. There is no metaphysical roots of Conspiracy but historical causes founded in the social and economic relations. 6. Regional and international powers put a further nail in the coffin of conspiracy on Syria.